Andung-Andung Ni Sordam - Purba, Albiner; Sina, Ibnu; Munafri, Sastra (Musica: Journal of Music, 2023)
Komposisi musik Andung-andung Ni Sordam merupakan komposisi yang terinspirasi dari instrumen musik tradisional dan kesenian tradisional Batak Simalungun yaitu Sordam dan Andung-andung. Komposisi ini menggunakan idiom musik dan karakter suara alat musik Sordam. Andung-Andung Ni Sordam merupakan musik komposisi gaya Fantasia yang digarap dalam bentuk tiga bagian dengan format orkestra. Dalam komposisi musik ini melodi dan pola ritme yang berangkat dari Andung-andung dan Sordam diambil sebagai gagasan yang digarap dalam sebuah komposisi musik instrumental. Dalam penggarapan komposisi musik Andung-andung Ni Sordam digunakan beberapa teknik pengolahan variasi motif seperti repitation, sequencing, imitasi, interpolasi, permutasi dan teknik komposisi seperti conterpoint,  ABSTRACTThe composition of music Andung-andung Ni Sordam is a composition inspired by instrument music traditional and traditional arts Batak Simalungun namely Sordam and Andung-andung.  This composition uses musical idioms and the sound characters of Sordam instruments. Andung-Andung Ni Sordam is a composition music with a Fantasia style worked in the form of three parts with an orchestral format. In this musical composition, melodies and rhythm patterns that depart from Andung-andung and Sordam are  taken as ideas that are worked on in an instrumental music composition. In the cultivation of Andung-andung Ni Sordam music composition,  several techniques for processing variations of motifs such as repitation, sequencing, imitation, interpolation, permutations and compositional techniques such as conterpoint, without losing the characteristics of Andung-andung and Sordam music